Suplementasi Sabun Mineral dan Mineral Organik serta Kacang Kedelai Sangrai pada Domba - . Adawiah; T Sutardi; T Toharmat; W Manalu; . Nahrowi; U H Tanuwiria (Faculty of Animal Science, Bogor Agricultural University, 2006)
The objective of this study was to evaluate the use of mineral soap, organic mineral and roasted soybean supplementations to improve productivity in ruminant animals. Thirty two Garut Sheep (initial body weight 22.38 ± 3.56 kg) were assigned into a randomized block design with eight treatments. Body weight was used as a block (4 blocks). Eight rations evaluated in this trial were FO: basal diet + fish oil, CO: basal diet + corn oil, CaFO: basal diet + calcium soap of fish oil, CaCO: basal diet + calcium soap of corn oil, ZnFO: basal diet + zinc soap of fish oil, ZnCO: basal diet + zinc soap of corn oil, RS: basal diet + roasted soybeans, MM: basal diet + mineral mix. The experimental diets were fed for 8 weeks. The result of the experiment showed that calcium soap improved animal growth better than did zinc soap. Daily gains of sheep fed FO (99 g/d), CaFO (114 g/d), CaCO (103 g/d), RS (105 g/d), and MM (103 g/d), diets were higher (P < 0.01) than those of sheep fed CO (86 g/d), ZnFO (88 g/d), and ZnCO (53 g/d) diets. Dry matter intake of sheep fed CO (903 g/d), CaCO (947 g/d), RS (933 g/d) diets were higher (P < 0.01) than those fed FO (820 g/d), CaFO (856 g/d), ZnFO (847 g/d), ZnCO (785 g/d), and MM (805 g/d) diets. Dry matter digestibility of CO (70%) and CaFO diet (76%) were higher (P < 0.01) than other diets. Nitrogen retention of sheep fed CaFO (11.8 g/d), RS (12.2 g/d), and MM (13.2 g/d) diets were higher (P < 0.01) than those fed FO (10 g/d), CO (10 g/d), CaCO (9.8 g/d), ZnFO (9.0 g/d), and ZnCO (9.0 g/d) diets. Organic mineral, calcium soap of fish oil, calcium soap of corn oil, and roasted soy bean supplementation increased daily gain up to 105 g/d. It was concluded that calcium soap, organic mineral and roasted soybean improved growth of sheep.Key words : soap, oil, mineral, roasted soy bean, sheep